PENGARUH PEMANFAATAN SISTEM INFORMASI AKADEMIK (AIS) TERHADAP KINERJA INDIVIDUAL DENGAN KEMUDAHAN PENGGUNA SEBAGAI VARIABEL MODERATOR - Rahmat Rizkiyanto (ETIKONOMI, 2014)
This research purpose to determine whether the existing Information Systems (AIS), which in this case is a AIS affects individuals performance is moderated by the ease of use . Research instrument in this study is a questionnaire with variables measuring based on a Likert scale. Questionnaire was tested with reliability and validity test. Then the classical assumption test questionnaire covering normality test and Multicolinearity Test. Absolute value difference test was conducted to test the hypothesis. From the results of tests performed, showed that the variable of use of AIS give significant positive effect on the performance of the individual. The variable of ease of use did not moderate the effect of the use of the  AIS on the performance of the individual , so it can be said that ease of use is not a variable moderatingDOI: 10.15408/etk.v13i1.1880